Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

2x + y = 7 - 9x + 6y = 0​

Sagot :

x=2

Step-by-step explanation:

y=7-2x -------(1)

6y=9x

y=9x/6 = 3x/2------(2)

Now,

Equation equation 1 and 2

7-2x= 3x /2

2(7-2x)=3x

14-4x=3x

14=4x+3x

14=7x

14/7=x

x=2